LASER SCANNING SHIHRAZAD'S BATHS: 1001 TALES OF ZANZIBAR NIGHTS. - Basell, Laura; Ali, Abdallah Khamis; Egberts, Ella; Firoozi-Nejad, Behnam; Mellor, Nicholas; Horton, Mark (Antiquaries Journal, 2020)
This article presents the first archaeological survey of the ornate Kidichi baths on Zanzibar. The baths were built either for or by Shihrazad, a wife of Zanzibar's nineteenth-century ruler Said bin Sultan (1806–56). Laser scanning the ornate plaster stucco clarified two inscriptions, the precise meaning of which had been lost. By combining archaeological survey results with historical research and a translation of the inscriptions, a new narrative is presented in which the main protagonist is, unusually, female. Her story raises a host of questions relating to heritage, gender, religion and politics in modern-day Africa and beyond.